Treatment outcomes and prognosis of patients with primary and acquired BRAF‐mutated non‐small cell lung cancer: A multicenter retrospective study. Issue 9 (23rd April 2022) - Wang, Wenxian; Gu, Xiaodong; Si, Jinfei; Pu, Xingxiang; Wang, Liping; Chen, Huafei; Xu, Chunwei; Zhang, Xiaoyan; Yuan, Hongling; Lou, Guangyuan; Shao, Lan; Zhang, Gu; et al.
Abstract: The incidence of primary and acquired BRAF mutations is low in non‐small cell lung cancer (NSCLC), with limited demographic and treatment outcome data available for this patient population. We evaluated lung cancer samples with programmed cell death ligand 1 (PD‐L1) information extracted from 12 051 cases (cohort A) of lung cancer from OncoPanscan™‐based sequencing of tissue (Genetron Health) and conducted retrospective multicenter data analysis using the database of Zhejiang Cancer Hospital and four other centers (cohort B, including 73 primary BRAF mutation and 14 acquired BRAF mutation cases) to compare treatment outcomes of patient groups with primary and acquired BRAF mutations. In cohort A, after propensity score analysis, 165 samples of NSCLC with BRAF mutations were screened along with 165 paired non‐BRAF mutation samples. We observed no significant differences in the proportion of samples with ≥1% PD‐L1 between BRAF and non‐BRAF mutant groups. The median progression‐free survival (mPFS) period in 13 patients with primary BRAF mutations receiving BRAF tyrosine kinase inhibitors (BRAF‐TKIs) was 7.0 months. The group with primary BRAF mutations receiving immune checkpoint inhibitor (ICI) combination chemotherapy had better PFS than those administered ICI monotherapy (14.77 months vs. 5.0 months, p = 0.025) and similar results were obtained for OS (unreached vs. 20.3 months, p = 0.013). For acquired BRAF mutations, mPFS of BRAF‐TKI, ICI‐based, and chemotherapy‐based regimens were 3.8, 1.5, and 1.9 months, respectively. Therefore, for patients with the primary BRAF V600E mutation, targeted therapy or immunochemotherapy could serve as effective treatment choices, while for those with acquired BRAF V600E, targeted drug therapy may remain the preferred solution in China.